Flicker Compensation for Archived Film Sequences Using a Segmentation-Based Nonlinear Model. (11th November 2008) - Forbin Forbin, Guillaume Guillaume; Vlachos Vlachos, Theodore Theodore
Abstract : A new approach for the compensation of temporal brightness variations (commonly referred to as flicker) in archived film sequences is presented. The proposed method uses fundamental principles of photographic image registration to provide adaptation to temporal and spatial variations of picture brightness. The main novelty of this work is the use of spatial segmentation to identify regions of homogeneous brightness for which reliable estimation of flicker parameters can be obtained. Additionally our scheme incorporates an efficient mechanism for the compensation of long duration film sequences while it addresses problems arising from varying scene motion and illumination using a novel motion-compensated grey-level tracing approach. We present experimental evidence which suggests that our method offers high levels of performance and compares favourably with competing state-of-the-art techniques.